A Comprehensive Empirical Study of the UK Electricity Markets: Retail, Wholesale, and Balancing Perspectives - Huanhuan Chen (2024)
This thesis provides a thorough empirical analysis of the UK electricity market focusing on retail, wholesale, and imbalance prices. Chapter 2 reveals that the declined concentration pushed retail prices up while the cost of consumer-funded schemes raised prices. The results suggest that large suppliers raised retail prices due to higher indirect costs from decreased sales (market share). Still, competition from smaller suppliers limited the incumbent’s ability to increase prices and receive lower profit margins. This indicates that competition does not directly lower prices; instead, it affects the existing behaviours and pricing strategies within the retail electricity markets. In Chapter 3, the coexistence of Renewables Obligation and Contracts for Difference schemes for supporting wind farms creates a unique market scenario. This study shows that the wind generation supported by the Contracts for Difference scheme significantly decreases wholesale prices due to aggressive pricing, taking advantage of the scheme's design. This trend negatively impacts the profitability and competitiveness of Renewables Obligation supported wind farms. These insights highlight the need for policymakers to ensure a balanced approach that protects the interests of all market participants while fostering investor confidence. Chapter 4 explores the factors determining the high imbalance prices, motivated by large increases in imbalance prices since 2016. The results suggest that lower de-rated margins lead to higher imbalance prices, higher imbalance volumes correlate with increased imbalance prices, and rising intraday prices are linked to higher imbalance prices. Key findings indicate that imbalance price surges are linked to broader market trends rather than imbalances within the balancing market itself, suggesting potential regulatory adjustments and arbitrage opportunities. Keywords: Consumer-funded schemes; Market concentration; Indirect costs; Retail price; Contract for Difference; Renewable Obligation; Wholesale Electricity Prices; Aggressive pricing; Regulatory Risks; Imbalance Prices; Intraday Prices; Balancing Mechanism.